Comparative anti-androgenic actions of vinclozolin and flutamide on transgenerational adult onset disease and spermatogenesis - Anway, Matthew D. (Reprod Toxicol, 2008)
Exposure of gestating female rats to the anti-androgenic endocrine disruptor vinclozolin has been shown to induce transgenerational adult onset disease phenotypes. The current study, was designed to compare the actions of vinclozolin to the known anti-androgenic compound flutamide. The gestating female rats were exposed to intraperitoneal injections during embryonic day 8–14 (E8–E14) to 100 mg/kg/day vinclozolin or flutamide at either 5mg or 20 mg/kg/day. As previously observed, vinclozolin induced a transgenerational testis phenotype of increased spermatogenic cell apoptosis and decreased epididymal sperm number. In contrast, the flutamide exposures resulted in a testis phenotype of increased spermatogenic cell apoptosis and decreasedepididymal spermnumbers in the F1 generation only, and not the F2 and F3 generation adult males. Interestingly, some of the lowdose (5 mg/kg) flutamide F2 generation offspring developed spinal agenesis and supernummery development (polymelia) of limbs. Although the actions of vinclozolin and flutamide appear similar in the F1 generation males, the transgenerational effects of vinclozolin do not appear to be acting through the same anti-androgenic mechanism as flutamide.